Intrahospital transfers and the impact on nursing workload. Issue 23 (10th July 2017) - Blay, Nicole; Roche, Michael A; Duffield, Christine; Gallagher, Robyn
Abstract: Aims and objectives: To determine the rate of patient moves and the impact on nurses' time. Background: Bed shortages and strategies designed to increase patient flow have led to a global increase in patient transfers between wards. The impact of transferring patients between wards and between beds within a ward on nurses' workload has not previously been measured. Design: A two‐stage sequential study. Retrospective analysis of hospital data and a prospective observational‐timing study. Methods: Secondary analysis of an administrative data set to inform the rate of ward and bed transfers ( n  = 34, 715) was undertaken followed by an observational‐timing study of nurses' activities associated with patient transfers ( n  = 75). Results: Over 10, 000 patients were moved 34, 715 times in 1 year which equates to an average of 2.4 transfers per patient. On average, patient transfers took 42 min and bed transfers took 11 min of nurses' time. Based on the frequency of patient moves, 11.3 full‐time equivalent nurses are needed to move patients within the site hospital each month. Conclusion: Transferring patients is workload intensive on nurses' time and should be included in nursing workload measurement systems. Relevance to clinical practice: Nurses at the site hospital spend over 1700 hr each month on activities associated with transferring patients, meaning that less time is available for nursing care.